Alternative splicing and genetic variation of mhc-e: implications for rhesus cytomegalovirus-based vaccines - Hayden Brochu; Ruihan Wang; Tammy Tollison; Chul-Woo Pyo; Alexander Thomas; Elizabeth Tseng; Lynn Law; Louis J. Picker; Michael Gale; Daniel E. Geraghty; Xinxia Peng (Communications Biology, 2022)
The alternative splicing and genetic variations across the whole MHC-E locus of Rhesus Macaques (Mamu-E) are analysed, which provides a foundation for more comprehensive research of Mamu-E and informs translational research of CMV-based vaccines.